Reasons for taking wrong decisions in football assistant referee during the determination of offside - Абдула [Anatoliy Abdula] Анатолій Борисович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Purpose: to educe principal reasons of acceptance of wrong decisions the assistants of arbiter in football at determination of offside. Decisions are analysed more than 70 assistants of arbiter during realization of soccer matches of different qualification. The basic causes of wrong decisions in football assistant referee in determining player in the offside. Analyzed more than 70 assistants referees during football matches of different skills. It is proved that wrong decisions assistants depend on the choice of the penultimate position on the defensive player. Ahead or behind the line of the player changes the angle of view and distorts its correct perception. It is established that the domestic assistant referees more wrong in fixing the position of offside in the penultimate line of the backlog of player defense, that explain insufficient physical condition. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>